Chemical identification of an active component and putative neural mechanism for repellent effect of a native ant’s odor on invasive species - Uebi, Tatsuya; Sakita, Tomoya; Ikeda, Ryo; Sakanishi, Keita; Tsutsumi, Tomoaki; Zhang, Zijian; Ma, Huiying; Matsubara, Ryosuke; Matsuyama, Shigeru; Nakajima, Satoko; Huang, Rong-Nan; Habe, Shunya; et al. (Frontiers in Physiology, 2022)
The invasive Argentine ants (Linepithema humile) and the red imported fire ants (Solenopsis invicta) constitute a worldwide threat, causing severe disruption to ecological systems and harming human welfare. In view of the limited success of current pest control measures, we propose here to employ repellents as means to mitigate the effect of these species. We demonstrate that cuticular hydrocarbons (CHCs) used as nestmate-recognition pheromone in the Japanese carpenter ant (Camponotus japonicus), and particularly its (Z)-9-tricosene component, induced vigorous olfactory response and intense aversion in these invasive species. (Z)-9-Tricosene, when given to their antennae, caused indiscriminate glomerular activation of antennal lobe (AL) regions, creating neural disarray and leading to aversive behavior. Considering the putative massive central neural effect, we suggest that the appropriate use of certain CHCs of native ants can facilitate aversive withdrawal of invasive ants.